DESIGN AND BUILD SALAK (Salacca Sumatrana) EMBALMING MACHINE WITH CONVEYOR - Riri Syavira; Tiaminah Nasution; Raisa Nabila; Rita Juliani (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2018)
It has been done the manufacture of Salak embalming machine for partners of Lopo Salak in Padangsidempuan.This machine can be used to assist partners in the process of embalming Salak to produce good quality and guaranteed freshness. The steps in the manufacture of this machine start from the design, the provision of tools and materials, manufacture and test the machine. The results show that the machine works optimally with the average production of salak 25 kg/hour due to embalming. In addition, the embalming machine has a propulsion engine that serves as the embalming and drying of Salak.